Translation initiation with 70S ribosomes: an alternative pathway for leaderless mRNAs - Moll, Isabella (Oxford University Press, 2004)
It is generally accepted that translation in bacteria is initiated by 30S ribosomal subunits. In contrast, several lines of rather indirect in vitro evidence suggest that 70S monosomes are capable of initiating translation of leaderless mRNAs, starting with the A of the initiation codon. In this study, we demonstrate the proficiency of dedicated 70S ribosomes in in vitro translation of leaderless mRNAs. In support, we show that a natural leaderless mRNA can be translated with crosslinked 70S wild-type ribosomes. Moreover, we report that leaderless mRNA translation continues under conditions where the prevalence of 70S ribosomes is created in vivo, and where translation of bulk mRNA ceases. These studies provide in vivo as well as direct in vitro evidence for a 70S initiation pathway of a naturally occurring leaderless mRNA, and are discussed in light of their significance for bacterial growth under adverse conditions and their evolutionary implications for translation.